Polycyclic aromatic hydrocarbons (PAHs) levels and toxicity in herbal teas marketed in Malaysia using QuEChERS and GC-FID - Azrina Aziz,; Khairiah Abd Karim,; Mohd Azmier Ahmad,; Mohamad Jemain Mohamad Ridhwan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
In line with the growing health trend in Malaysia, more consumers drink herbal tea for medicinal benefits. However, herbal tea products could be contaminated with polycyclic aromatic hydrocarbons (PAHs) from various production sources. There is a little study focused on the detection of PAHs in herbal tea species distributed in Malaysia. This study was performed to investigate PAHs content and toxicity in selected commercial herbal teas in Malaysia. A total of seven different Malaysian herbal tea samples were extracted using QuEChERS extraction method and the contamination level of PAHs were evaluated using gas chromatography (GC) with a flame ionization detector (FID). The total content of 10 PAHs (Σ10PAHs) in the herbal tea samples ranged from 2.53 to 9.39 μg/kg. Acenaphthene, fluorene, phenanthrene and anthracene were the most abundant compounds with 53% contribution of all PAHs content. All tested herbal teas species showed low toxic equivalency (TEQ) values ranging from 0.0027 to 0.1148. The least contaminated samples were Strobilanthes crispus, Senna alata, Orthosiphon aristatus, Clinacanthus nutans, and Stevia rebaudiana.